2020
DOI: 10.1177/1357034x20923017
|View full text |Cite
|
Sign up to set email alerts
|

What More Do Bodies Know? Moving with the Gendered Affects of Place

Abstract: This article focuses on what bodies know yet which cannot be expressed verbally. We started with a problem encountered during conventional interviewing in an ex-mining community in south Wales when some teen girls struggled to speak. This led us to focus on the body, corporeality and movement in improvisational dance workshops. By slowing down and speeding up video footage from the workshops, we notice movement patterns and speculate about how traces of gender body-movement practices developed within mining co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…However, from a feminist new materialist perspective, the more important question is how the relationships, and socio-political contexts in which they are lived, fix or expand the capacities of bodies involved in them (e.g. Ivinson and Renold 2021).…”
Section: Surfacing Haptic Memories Of Hurt Through Power Boxesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, from a feminist new materialist perspective, the more important question is how the relationships, and socio-political contexts in which they are lived, fix or expand the capacities of bodies involved in them (e.g. Ivinson and Renold 2021).…”
Section: Surfacing Haptic Memories Of Hurt Through Power Boxesmentioning
confidence: 99%
“…Furthermore, we propose that the minor gestural movements in the processes of making art and crafts allowed for changes in the girls' somatic archives (Paasonen 2013), understood as temporally accumulating, corporeal-affective capacities, which enabled them to assert both desire and damage more effectively in relation to boys. Overall, we draw on feminist new materialist research and activism concerning young people's sexual cultures Pihkala, Huuki, and Sunnari 2019;Ivinson and Renold 2021;Renold 2018;Renold and Ringrose 2019;Strom et al 2019). In this framework, bodies are understood as continuously becoming and transforming through their affective relations with other human and non-human entities, material objects, spaces, histories, and discourses (e.g.…”
mentioning
confidence: 99%
“…Women developed routines to make mundane work bearable and in so doing formed collective habits of sociality, such as, sweeping front steps, washing clothes and baking on specific days of the week (Walkerdine & Jimenez, 2012). We have referred to these patterns, rhythms and routines of community life as a community beat (Ivinson & Renold, 2021).…”
Section: Affective Mattersmentioning
confidence: 99%
“…While undertaking ethnographic work in classrooms we observed that some young people and especially boys found it difficult to settle themselves in lessons. In contrast, we were struck by girls' docile bodies within school (Ivinson & Renold, 2020, 2021. For example, Gwaun (pseudonym, age 14) told us that when he found the pressure and social interactions at school too challenging he absented himself from school and went to work on his aunt's building project.…”
Section: Line Of Flight 1: Troubled Landscapesmentioning
confidence: 99%
See 1 more Smart Citation